2009
DOI: 10.1084/jem.20082745
|View full text |Cite
|
Sign up to set email alerts
|

Transcellular migration of leukocytes is mediated by the endothelial lateral border recycling compartment

Abstract: Leukocyte migration across endothelial cell borders (paracellular) and through endothelial cells (transcellular) appear to be distinct processes. During paracellular migration, membrane from a parajunctional reticulum of interconnected vesicles, the endothelial lateral border recycling compartment (LBRC), moves to surround the leukocyte in a kinesin-mediated, microtubule-dependent manner. We show that transcellular migration likewise requires targeted trafficking of LBRC membrane. We show that in addition to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
177
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(186 citation statements)
references
References 40 publications
8
177
1
Order By: Relevance
“…In this context, it is worth noting that as leucocytes cross the endothelium, they become surrounded by the lateral border recycling compartment (LBRC), an interconnected reticulum of membrane that functions as a 'channel.' This channel is lined with several proteins, namely PECAM (platelet endothelial cell adhesion molecule), CD99 (cluster of differentiation 99) and JAM-A but not VE-cadherin which appeared to be endocytosed (Xiao et al 2005;Gavard & Gutkind 2006), that are needed for leucocytes to cross the endothelium (Mamdouh et al 2003(Mamdouh et al , 2008(Mamdouh et al , 2009. Interestingly, depolymerization of microtubules blocked the accumulation of the LBRC around leucocytes and transmigration (Mamdouh et al 2009).…”
Section: Germ Cell Movement Across the Btb: Insights From Virus And Cmentioning
confidence: 99%
“…In this context, it is worth noting that as leucocytes cross the endothelium, they become surrounded by the lateral border recycling compartment (LBRC), an interconnected reticulum of membrane that functions as a 'channel.' This channel is lined with several proteins, namely PECAM (platelet endothelial cell adhesion molecule), CD99 (cluster of differentiation 99) and JAM-A but not VE-cadherin which appeared to be endocytosed (Xiao et al 2005;Gavard & Gutkind 2006), that are needed for leucocytes to cross the endothelium (Mamdouh et al 2003(Mamdouh et al , 2008(Mamdouh et al , 2009. Interestingly, depolymerization of microtubules blocked the accumulation of the LBRC around leucocytes and transmigration (Mamdouh et al 2009).…”
Section: Germ Cell Movement Across the Btb: Insights From Virus And Cmentioning
confidence: 99%
“…Therefore, VVOs and caveolae have been considered as fundamental membrane fusion elements for pore formation during the transcellular migration (21). On the other hand, the unique structural figures called "lateral border recycling compartment-LBRC" were distinct from VVOs (22,23) and could function as a cellular storage for some of adhesion molecules including PECAM, CD99 and JAM-A (24). It has been reported that LBRC is essential for paracellular and transcellular migration of lymphocytes in a microtubule-dependent manner (24).…”
Section: Electron Micrographs Of a "High" Endothelial Cell In The Lummentioning
confidence: 99%
“…On the other hand, the unique structural figures called "lateral border recycling compartment-LBRC" were distinct from VVOs (22,23) and could function as a cellular storage for some of adhesion molecules including PECAM, CD99 and JAM-A (24). It has been reported that LBRC is essential for paracellular and transcellular migration of lymphocytes in a microtubule-dependent manner (24). Our ultrastructural results showed that some vesicular organizations at the borders of resting endothelial cells are structurally similar to LBRCs (Figure 2a,c,d).…”
Section: Electron Micrographs Of a "High" Endothelial Cell In The Lummentioning
confidence: 99%
“…In this case, the level of neutrophil activation and subsequent activation of specific intracellular signals may be an important determinant factor. The fact that intradermal injection of fMLP stimulates transcellular migration in vivo (Feng et al, 1998), or that direct activation by fMLP of neutrophils plated on endothelial cells increases transcellular migration events in vitro (Mamdouh et al, 2009) support this idea that transcellular migration can be promoted when neutrophils are highly activated. Because the strength of stimuli-induced intracellular signals can trigger various cellular responses, it is possible that high neutrophil activation may promote invasive actin protrusions to form in tissue environment with loose endothelial junctions, and increase their ability to migrate transcellularly.…”
Section: Lps-induced Lung Inflammationmentioning
confidence: 99%
“…Akt signal strength may promote MMP release and convert noninvasive lamellipodial protrusions into invasive podosome structures. Because transcellular migration requires the formation of a transcellular channel and membrane fusion of the endothelial lateral border recycling compartment (LBRC; Mamdouh et al, 2009), Akt-driven invasive protrusions may send signals to endothelial cells to recruit the LBRC and initiate the formation of the transcellular pore away from the junction. Our findings strongly suggest that Rap1b loss directly increased the ability of neutrophils to exploit the transcellular pathway by enhancing intracellular signaling intensity.…”
Section: Lps-induced Lung Inflammationmentioning
confidence: 99%